DNA analysis of partial hydatidiform mole revealing triandric monogynic tetraploidy - Gergely, Lajos; Korbeľ, Miroslav; Repiská, Vanda; Danihel, Ľudovít; Hutník, Juraj; McCullough, Liam; Priščáková, Petra (Ceska gynekologie, 2023)
The authors present a case of a partial hydatidiform mole where DNA analysis (STR - short tandem repeat genotyping) showed a triandric monogynic tetraploid genome composition with a XXXY gonosomal complement. This genetic finding clinicopathologically correlates with a partial hydatidiform mole, although it is rare in comparison with the typical, diandric monogynic triploid partial moles. The genetic analysis definitively confirmed the suspected diagnosis of a partial mole. To exclude the possibility that molar pregnancy represented retained products of conception after elective pregnancy termination, STR profiles from molar pregnancy and previous products of conception were compared. Short tandem repeats genotyping is a useful molecular genetic method in the differential diagnosis of partial hydatidiform moles, where clinical-pathological findings are frequently ambiguous.
Keywords: Tetraploidy; Fertilization; Uterine Neoplasms; Female; partial hydatidiform mole; DNA analysis; těhotenství; nádory dělohy; mola hydatidosa; ženské pohlaví; DNA; fertilizace; short tandem repeat genotyping; Pregnancy; Hydatidiform Mole; retained product of conception; lidé; Humans; tetraploidie